Pathological Impacts Due to The Existence of Plastic Waste in Rumen of Bali Cattle - Berata , I Ketut; Susari, Ni Nyoman Werdi; Kardena, I Made; Novianti, Arindita Niatazya (Jurnal Medik Veteriner, 2023)
This study aimed to determine the prevalence of Bali cattle rumen containing plastic waste and its impact on tissues and health risks. A total of 100 Bali cattle were investigated after being slaughtered at several traditional slaughterhouses in Denpasar City. Rumen samples were examined for any plastic waste, meanwhile blood, liver, kidney, lungs, spleen, intestine, and myocardium were collected for evaluation of heavy metals content and histopathological examination. The heavy metal measurement was performed using the atomic absorption spectrophotometry (AAS) method. Those tissues for histopathological examination were fixed in buffer neutral formalin (BNF) and then evaluated using hematoxylin-eosin (HE) staining. The results of the examination reported 9 rumens (9%) containing plastic waste. The hematological profile showed leucocytosis and the content of lead (0.841 ± 0.522 ppm). Histopathological changes in the liver, kidneys, lungs, spleen, and intestine, were found in various types of degeneration, inflammation, and mild necrosis. In conclusion, the prevalence of plastic waste in the rumen of Bali cattle was 9%, with leucocytosis, lead content was 0.841 ± 0.522 ppm, and various histopathological lesions such as congestion, inflammation, and fatty degeneration in parenchymous tissues.